THE STRUCTURING OF ORGANIZATIONAL AND DOCTRINE OF STATE DEFENSE IN FACING HYBRID WARFARE - Novky Asmoro; Andi Sutomo; Teguh Haryono; Rizki Putri (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Defense Doctrine and Strategy are designed to be able to synergize the performance of military and non-military components to protect and maintain Indonesia's national interests. The current doctrine of the Indonesian Armed Forces (TNI) Military Campaign is still dominant in dealing with military threats, even though based on the 2018 Indonesian Defense White Paper, the TNI must also be able to deal with hybrid threats. With its adaptive nature to changing threats, problems will arise if the military campaign doctrine has not accommodated the TNI's strategy and way of acting in dealing with hybrid threats. The defense doctrine must be able to accommodate the integration of military and non-military components is facing various types of warfare and threats such as military threats, non-military threats, and hybrid threats. Especially for the kind of hybrid threats namely cyber threats, terrorism, and other unconventional threats. Through an analytical descriptive analysis based on qualitative methods, it is hoped that the proper organization and doctrine will be disentangled in the face of this model war. Indonesian Armed Forces (TNI) as the war organizations that prioritize a modern universal perspective are a necessity as one of the efforts offered. This needs to be supported by the doctrine of national defense which accurately defines how an effort against hybrid warfare can transform from conventional to unconventional warfare and the actors involved.  Military or TNI organizations that prioritize a modern universal perspective are supported by the doctrine of national defense which accurately maps how an effort against hybrid warfare could transform from conventional warfare to unconventional.